EDUKASI SOPAN SANTUN BERBASIS NILAI-NILAI PANCASILA MELALUI MEDIA LAGU PADA SISWA-SISWI SD BINONG 1 - Situngkir, Adventina; Mangilaleng, Juliana Tirza (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
This community service program aims to educate students of SD Binong 1 about manners based on Pancasila values through song media. Pancasila, as the foundation of the Indonesian state, has five precepts that contain moral values that are very important to be applied in everyday life. This education was given because it was confirmed that there were acts of bullying between friends, which used physical appearance as a mockery. During the observation, some students were seen and heard to use inappropriate or abusive words. The method used in this program is counseling and singing training conducted in several sessions. Each session combines theoretical explanations about manners based on Pancasila values with fun and interactive singing activities. The songs chosen contain lyrics that teach the importance of having a good attitude, respecting parents, and helping others, all of which are reflections of Pancasila values. The results of this activity show that the approach through song media can be well received by students, and they more easily understand and remember the values taught. In addition, students' active involvement in this activity also increased their enthusiasm and motivation in learning.